REVISITING ZIONISM AS A STATE IDEOLOGY OF ISRAEL: A CRITICAL EXAMINATION OF THE ISRAEL—PALESTINE CONFLICT - Sabiq Musthafa (CMES (Center of Middle Eastern Studies), 2024)
This paper critically examines Zionism as the state ideology of Israel, with a particular focus on its role and impact within the Israel-Palestine conflict. Zionism, originally a movement for the re-establishment of a Jewish homeland, has evolved into a complex and contentious political ideology. This study revisits its historical roots, ideological foundations, and contemporary interpretations. By exploring the intersection of Zionism with nationalism, religion, and politics, the paper aims to provide a nuanced understanding of how Zionism shapes Israeli policies and influences the ongoing conflict with Palestine. The analysis delves into the narratives and counter-narratives surrounding Zionism, addressing the perspectives of various stakeholders, including Israeli Jews, Palestinians, and the international community. Through a critical lens, the paper assesses the implications of Zionist ideology for peace prospects, human rights, and regional stability. The findings underscore the need to re-evaluate Zionism in light of its practical outcomes and ethical considerations. This study contributes to the broader discourse on state ideologies, conflict resolution, and Middle Eastern politics, offering insights into the possibilities for a just and sustainable resolution to the Israel-Palestine conflict.